Western Cultural Symbols in Latin American and Chicano Literature : an Historical and Semiotic Analysis. - Breining, Daniel (Edwin Mellen Press, 2010)
This book explains the fundamentals of semiotic theory (the study of signs), and applies it to more than twenty works by a dozen Latin American and Mexican American authors. Using a post-modernist interpretation of signs, Breining makes the point that there exists a relationship of the privileged and disenfranchised within Latin America and Chicano literature. Covering a span of more than five hundred years, from pre-Hispanic times to the late twentieth century, Breining demonstrates how the signs found with the literature of each period of Latin American history, define social interactions, c.